TRANSLATION QUALITY IN INTERNATIONAL LARGE-SCALE ASSESSMENTS IN EDUCATION: Received: 04th September 2021; Revised: 01st December 2021, 10th January 2022; Accepted: 11th January 2022 - Liçi, Luela (PEOPLE: International Journal of Social Sciences, 2022)
During the last 20 years, large-scale international assessments in education became part of international research. The increased number of countries participating in the international studies of PISA, TIMSS, and PIRLS and translation of their assessment instruments in many languages of the world is accompanied by the request to ensure translation quality. Translation quality and its management became and are an important concern for the PISA, TIMMS, and PIRLS. The linguistics quality control centres have developed translation policies, standards, and procedures. This paper aims to present the translation policy and translation quality procedures implemented by PISA, TIMSS, and PIRLS in the last 20-years. The paper is focused on the need for translation quality and illustrates how translation quality is implemented in practice. The paper is based on the translation guidelines, secondary data from the technical reports of these international assessment studies, and recent research findings. This paper concludes that the suitable policy and procedures of translation quality used by PISA, TIMSS, and PIRLS have provided a high quality of translated instruments that has enabled the comparison of assessment results. The article also highlights PISA’s, TIMSS’s, and PIRLS’s contribution to the development of translation quality theory and practice of the educational materials.